Efisiensi Penggunaan Daya Listrik Di Hotel Carrissima Palembang - Daeny Septi Yansuri; Dian Eka Putra; Subianto Subianto; Rio Anggara (Jurnal Ampere, 2023)
The research was conducted by assuming when the hotel room was fully occupied by guests. This research is to find out in more detail about the use of energy, especially for electrical energy at the Carrissima Hotel Palembang, to find out and implement energy saving opportunities and increase the efficiency of electricity use. The research method used is the literature method, interview method, and observation method. From the calculations carried out, the results obtained for hotel lighting, especially in the hotel lobby, cannot be said to be effective in the use of electrical energy, from the calculations obtained the intensity of lighting is 16.25 Watt/m2, while the maximum limit specified is 20 Watt/m2, while for rooms hotels, the intensity of lighting is 5.16 Watt/m2, while the maximum limit specified is 17 Watt/m2. So the intensity of the Carrissima hotel room does not have an indication of energy wastage, but it is not efficient, lastly for the use of Air Conditioning (AC) at the Carrissima hotel, from the results of these calculations based on the Energy Consumption Index (IKE), where the level of comfort and energy saving in air-conditioned buildings is 23.75 to 37.75 W/m2. The use of air conditioning at the Carrissima hotel is above the convenience of wasting energy. The highest AC power intensity is on the 2nd and 3rd floors, which is 18.33 W/m2, while the lowest intensity is on the 1st floor, which is 1.38 W/m2.